2013
DOI: 10.1063/1.4791600
|View full text |Cite
|
Sign up to set email alerts
|

Size effects in thin gold films: Discrimination between electron-surface and electron-grain boundary scattering by measuring the Hall effect at 4 K

Abstract: We report the Hall effect measured in gold films evaporated onto mica substrates, the samples having an average grain diameter D that ranges between 12 and 174 nm, and a thickness t of approximately 50 nm and 100 nm. The Hall mobility was determined at low temperatures T (4 K ≤ T ≤ 50 K). By tuning the grain size during sample preparation, we discriminate whether the dominant collision mechanism controlling the resistivity of the samples at 4 K is electron-surface or electron-grain boundary scattering, based u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…In a previous work, 12 we performed systematic measurements on the temperature and film thickness dependences of the resistivity and concluded that the dominant contributions to the resistivity are from grain boundary scattering and phonon scattering when the average grain size is smaller or comparable to film thickness. This result is consistent with other recent works, 13 which also found that the grain boundary scattering constitutes the most dominant contribution to the resistivity at low temperatures. In the present work, we present detailed measurements of the classical MR of Au films over wide temperature and thickness ranges.…”
Section: Introductionsupporting
confidence: 94%
“…In a previous work, 12 we performed systematic measurements on the temperature and film thickness dependences of the resistivity and concluded that the dominant contributions to the resistivity are from grain boundary scattering and phonon scattering when the average grain size is smaller or comparable to film thickness. This result is consistent with other recent works, 13 which also found that the grain boundary scattering constitutes the most dominant contribution to the resistivity at low temperatures. In the present work, we present detailed measurements of the classical MR of Au films over wide temperature and thickness ranges.…”
Section: Introductionsupporting
confidence: 94%
“…Unfortunately STM measurements, which could provide a direct number for this parameter, are only possible in flat regions of the films, which are not representative of the density of adsorbed molecules on the "hut" topography. Higher sensitivity of a "hut" type topography in electrical transport of thin films is indeed not a rare occurrence, since it has also been observed in galvanomagnetic transport in gold thin films [28].…”
Section: T (Nm) T S /T a (°C) Surface Roughness (Nm)mentioning
confidence: 97%
“…In the case of nanocrystalline Co basic films, the size dependences of the specific conductance for the Co films with and without the Ni coating calculated by relations (5) and (6) demonstrate that the deposition of a thin Ni coating results in an increase of their specific conductance (Fig. 3, c).…”
Section: Results and Their Discussionmentioning
confidence: 86%
“…In particular, it was shown that the size restriction in films and nanostructures gives rise to the appearance of some physical effects, which are weakly pronounced or not observed at all in massive specimens. As a rule, the surface scattering of charge carriers is described in the framework of the semiclassical approach [6,7]. In so doing, some electrons are supposed to be reflected specularly and the others diffusively by the film surface, with the coefficient of specular reflection from the surface varying from 0 to 1.…”
Section: Introductionmentioning
confidence: 99%